Impact of singly occupied molecular orbital energy on the n-doping efficiency of benzimidazole derivatives - Riera-Galindo, Sergi; Orbelli Biroli, Alessio; Forni, Alessandra; Puttisong, Yuttapoom; Tessore, Francesca; Pizzotti, Maddalena; Pavlopoulou, Eleni; Solano, Eduardo; Wang, Suhao; Wang, Gang; Ruoko, Tero-Petri; Chen, Weimin M.; et al. (ACS applied materials & interfaces, 2019)
We investigated the impact of singly occupied molecular orbital (SOMO) energy on the n-doping efficiency of benzimidazole derivatives. By designing and synthesizing a series of new air-stable benzimidazole-based dopants with different SOMO energy levels, we demonstrated that an increase of the dopant SOMO energy by only ∼0.3 eV enhances the electrical conductivity of a benchmark electron-transporting naphthalenediimide-bithiophene polymer by more than 1 order of magnitude. By combining electrical, X-ray diffraction, and electron paramagnetic resonance measurements with density functional theory calculations and analytical transport simulations, we quantitatively characterized the conductivity, Seebeck coefficient, spin density, and crystallinity of the doped polymer as a function of the dopant SOMO energy. Our findings strongly indicate that charge and energy transport are dominated by the (relative) position of the SOMO level, whereas morphological differences appear to play a lesser role. These results set molecular-design guidelines for next-generation n-type dopants.